DETERMINATION OF AMOXYCYLLIN AND CLAVULANIC ACID IN PHARMACEUTICAL DOSAGE FORMS BY HPLC WITH AMPEROMETRIC DETECTION (Journal of Sciences, Islamic Republic of Iran)
A simple and sensitive high performance liquid chromatographic method with electrochemical detection is described for the quantitative determination of the amoxycillin and clavulanic acid in pharmaceutical dosage forms. Separation of sample components occurs on a reversed phase C18 column with a mobile phase consisting of methanol-water-phosphate buffer. For the amperometric detection, the potentials of +1.180 and +1.250 V were set on the working electrode for amoxycillin and clavulanic acid, respectively. High linearity over a concentration range of (25 ng to 250 ng, r = 0.998) and (31.25 ng to 1 µg, r = 0.999) was observed. This method is convenient and reproducible for analysis of these two components in different dosage forms.